2021
DOI: 10.2147/jpr.s345760
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Fracture Haemorrhage Aspiration for Percutaneous Vertebroplasty in Treating Osteoporotic Vertebral Compression Fractures

Abstract: Background A retrospective study aimed to introduce a new method for improving the diffusion degree of bone cement and to observe its clinical efficacy in percutaneous vertebroplasty treating osteoporotic vertebral compression fractures (OVCFs). Methods From January 2019 to March 2020, a total of 83 patients were enrolled and reviewed. The patients were divided into two groups according to the operation method. The clinical and radiographic parameters were recorded and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Several studies have focused on the degree of diffusion of bone cement, which exerts a significant impact on biomechanical aspects, such as the stability and mechanical properties of the fracture site. Some studies have shown that the asymmetric distribution of the vertebral body and excessive filling of cement volume lead to the transfer and switching of unilateral load, resulting in NVCF 40,41 . The height and strength of the vertebral body recovered well, and the risk of vertebral recompression decreased significantly when the bone cement was in contact with the upper and lower endplates 40,41 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have focused on the degree of diffusion of bone cement, which exerts a significant impact on biomechanical aspects, such as the stability and mechanical properties of the fracture site. Some studies have shown that the asymmetric distribution of the vertebral body and excessive filling of cement volume lead to the transfer and switching of unilateral load, resulting in NVCF 40,41 . The height and strength of the vertebral body recovered well, and the risk of vertebral recompression decreased significantly when the bone cement was in contact with the upper and lower endplates 40,41 .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that the asymmetric distribution of the vertebral body and excessive filling of cement volume lead to the transfer and switching of unilateral load, resulting in NVCF 40,41 . The height and strength of the vertebral body recovered well, and the risk of vertebral recompression decreased significantly when the bone cement was in contact with the upper and lower endplates 40,41 . At the same time, some experts believe that when the cement distribution is wide enough (i.e., the area between the midline and contralateral pedicle), unilateral PKP can significantly restore the height of the vertebral body and provide a good therapeutic effect 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the study showed that only less than 10% of patients in the surgical group obtained sustained pain relief after surgery, more than half of the patients obtained only short-term pain relief for less than 3 months, and about one-third of the patients had no pain relief after surgery, so the effect of surgical pain relief was not satisfactory. In patients with osteoporosis alone, the effect of PVP/PKP on pain relief has been inconsistently concluded in different studies, with most studies concluding that patients had significant pain relief within 1 year after surgery [ 26 , 27 ]. However, some studies have also concluded that there was no significant improvement in pain in the surgical group compared to the placebo group [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Steinmann et al [9] found no signi cant difference in stiffness and strength between unilateral and bilateral percutaneous kyphoplasty. Therefore, percutaneous kyphoplasty is becoming a common surgical option for the treatment of osteoporotic vertebral fractures [10][11]. Traditionally, retrobulbar kyphoplasty was performed by injecting polymethylmethacrylate bone cement through the working channel established by the pedicle on both sides.…”
Section: Introductionmentioning
confidence: 99%